Amorphophallus fontarumii (Araceae), a new species from Tanay Rizal, Luzon Island, Philippines. Issue 7 (30th May 2022) - Bulawin, Norilyn F.; Medecilo‐Guiang, Maria Melanie P.; Alejandro, Grecebio Jonathan D.
Abstract : As an addition to the diversity of Amorphophallus we here describe the recent discovery of A. fontarumii sp. nov. The distinct characteristics of the new species are described and compared to A. caudatus Bustamante et al. and A. minimus Bustamante et al. It differs from the other species by its miniature habit, very long tapered verruculose appendix, absence of a staminode, finely verruculose, long, thin and filiform appendix apex, globose ovary and irregular peltate stigma with one lobe.